A Reply to Gerard Loughlin’s ‘Catholic Homophobia’ - Pugeda, Teofilo Giovan S, III (Archīum Ateneo, 2022)
This article replies to the accusations of homophobia levelled against the Catholic Church by Loughlin in his article in Theology. In it, he critiques the ‘culture of the Catholic Church – as constituted through the Roman magisterium’, without considering a broader ecclesiology of the Church necessary to substantiate his generalized claim that ‘homophobia is … a matter of Christian culture, of Catholic culture’. As such, his claim must be contextualized by the normative considerations presented in this article.